The causes of stage expansion of WTI/Brent spread - Hong-Zhi Tian (KeAi Communications Co., Ltd., 2019)
Abstract Historically, the price of WTI crude oil futures has long been higher than that of Brent by $2/barrel, but the spread between 2011 and 2015 was reversed and expanded to $24/barrel. In order to analyze the difference between two crude oil price variables with the same trend and phase separation using one method of analysis, this paper constructs a dynamic comparative analysis framework using the method of time-point decomposition of fluctuation factors to determine the different reasons and amplitudes for monthly fluctuations in the two price systems in the sample interval. The study found that the sensitive response of Brent futures price indicators to the world’s crude oil supply resulting from the depletion of oil in the North Sea oil field prompted it to rise in 2011–2015. For the WTI price system, due to the increase in the US shale oil production after 2008 and the restrictions in domestic pipeline transportation capacity, the increase in the Cushing crude oil inventory caused downward pressure on the WTI price. With the lifting of the US crude oil export ban in December 2015, arbitrage space disappeared, and the spread between the two gradually narrowed.